The Evolution of Multicellularity (Taylor & Francis, 2022)
Among the most important innovations in the history of life is the transition from single-celled organisms to more complex, multicellular organisms. Multicellularity has evolved repeatedly across the tree of life, resulting in the evolution of new kinds of organisms that collectively constitute a significant portion of Earth's biodiversity and have transformed the biosphere. This volume examines the origins and subsequent evolution of multicellularity, reviewing the types of multicellular groups that exist, their evolutionary relationships, the processes that led to their evolution, and the conceptual frameworks in which their evolution is understood. This important volume is intended to serve as a jumping-off point, stimulating further research by summarizing the topics that students and researchers of the evolution of multicellularity should be familiar with, and highlighting future research directions for the field.
English
Keywords: Biology, life sciences; Cellular biology (cytology); Developmental biology; Evolution; Molecular biology; Major Evolutionary Transitions,Cellular Aggregations,Plasmodial Slime Molds,Polysphondylium Pallidum,Multicellular Group,Fruiting Body Morphology,Cellular Slime Mold Dictyostelium Discoideum,Cellular Slime Mold,Myxococcus Xanthus,Charophyte Algae,Animal Kingdom,Major Evolutionary Transitions,Fruiting Body,Aggregative Multicellularity,Unicellular Ancestor,Multicellular Species,Stalk Cells,Genotype Phenotype Map,Volvox Carteri,Dictyostelium Discoideum,Physarum Polycephalum,Modifier Allele,Collective Fitness,Apical Cells,Stalk Formation,Unicellular Species,Tryptophan Aminotransferase